ASSISTANCE IN THE PREPARATION OF THE TERRITORIAL MANAGEMENT REGENERATION PROGRAM PLAN BINTARAN CHURCH YOGYAKARTA - Hariwibowo, Ignatius Novianto; Sutarta, Agustinus Edi; Noventa, Oscar Chrismadian; Anggraeni Widjojo, Maria Rosa Ratna Sri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Planning for the regeneration of administrators in the church area is a very important strategic step to ensure the sustainability of service and effective leadership in the midst of the dynamics of the people. This challenge of regeneration is faced by the Church of Saint Joseph Bintaran Yogyakarta. As a church located in the middle of the city, the Bintaran Church has a problem with the number of young people and young families who are starting to get busy. Therefore, this service is carried out to formulate steps for territorial regeneration. This service uses a SWOT analysis approach as a basic framework with the focus group discussion (FGD) method to find problems and needs. The results of FGDs with several teritories show that most teritories have a strong foundation as a community, so that the pattern of regeneration can be flexible according to the needs of the people in the territory. Thus, the regeneration program that needs to be carried out is to increase informal meetings to strengthen the sense of community and leadership training